Pengaruh Media Permainan Truth or Dare (TOD) Terhadap Hasil Belajar Matematika Siswa Kelas V SD Inpres Kakaskasen II - Fifiana Debora Pengambu; Tellma Monna Tiwa; Roos Marie Stella Tuerah (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This study aims to determine the effect of Truth or Dare game media on mathematics learning outcomes of fifth-grade students of SD Inpres Kakaskasen II. This type of research is quantitative with the experimental method, which is pre-experimental using a one-group pretest-posttest design type. The subjects of this study were 32 fifth-grade students of SD Inpres Kakaskasen II, consisting of 15 male students and 17 female students. Sampling using a total sampling technique. The data collection technique was a test technique using pretest and posttest. The results of descriptive statistical data analysis showed the average value of the pretest was 50 while the posttest was 88. The results of hypothesis testing using the Wilcoxon test showed a significance value of 0.00 < 0.05. The results of this study prove that there is an effect of Truth or Dare game media on the learning outcomes of fifth-grade students of SD Inpres Kakaskasen II.